0674 Association between Sleep and Menstrual Problems in Chinese Female University Students. (12th April 2019) - Zhou, Junying; Xing, Xiaocun; Xue, Pei; Tang, Xiangdong
Abstract: Introduction: Sleep disturbance can impact an individual's daytime function and emotional well-being. Little is known about the association between sleep and menstruation in young females. We aimed to investigate the association between sleep disturbance and menstrual problems in Chinese female university students. Methods: A total of 1006 female university students aged 15-38 years (mean age = 21.7 ± 2.8 years) participated in this study. Sleep duration, sleep quality and insomnia symptoms were assessed by the Pittsburgh Sleep Quality Index (PSQI) and the Insomnia Severity Index (ISI). Mood disorders were rated using the Self-Rated Anxiety Scale (SAS) and the Self-Rated Depression Scale (SDS). A structured questionnaire was used to assess participants' demographics and menstrual related problems such as menstrual cycle interval, period irregularity, menstrual flow length, menstrual blood volume, and premenstrual syndrome. Results: The prevalences of menstrual irregular, more menstrual blood volume, menstrual flow length ≥7 days, period pain, and premenstrual syndrome were significantly higher in participants with sleep disturbance than in those without sleep disturbance (P < 0.05) . After adjusting for age, body mass index, smoking status, and mood disorders, poor sleep quality (odds ratio [OR] = 1.81, 95% confidence interval [CI] = 1.23-2.68) and insomnia symptoms (OR = 1.66, 95% CI = 1.12 - 2.45) were significantly associated with menstrual flow length ≥7 days. Insomnia symptoms (OR = 1.94, 95% CI = 1.29-2.92) were significantly associated with menstrual irregular. Poor sleep quality (OR =1.75, 95% CI = 1.12-2.72) were significantly associated with more menstrual blood volume. Additionally, poor sleep quality (OR =1.55, 95% CI = 1.02-2.35; OR =1.71, 95% CI = 1.30-2.24) and insomnia symptoms (OR =1.81, 95% CI = 1.22-2.70; OR =1.88, 95% CI = 1.42-2.49) were significantly associated with period pain and premenstrual syndrome, respectively. However, sleep duration was not significantly associated with menstrual problems. Conclusion: Our results suggest that sleep disturbance was associated with menstrual problems among Chinese female university students. More attention should be paid to improving the sleep quality and insomnia symptoms in individuals with menstrual problems. Support (If Any): No